Epidemiology of inherited epidermolysis bullosa in Germany. (1st November 2022) - Has, Cristina; Hess, Moritz; Anemüller, Waltraud; Blume‐Peytavi, Ulrike; Emmert, Steffen; Fölster‐Holst, Regina; Frank, Jorge; Giehl, Kathrin; Günther, Claudia; Hammersen, Johanna; Hillmann, Kathrin; Höflein, Bettina; et al.
Abstract: Background: Epidermolysis bullosa (EB) is a rare genetic disorder manifesting with skin and mucosal membrane blistering in different degrees of severity. Objective: Epidemiological data from different countries have been published, but none are available from Germany. Methods: In this population‐based cross‐sectional study, people living with EB in Germany were identified using the following sources: academic hospitals, diagnostic laboratories and patient organization. Results: Our study indicates an overall EB incidence of 45 per million live births in Germany. With 14.23 per million live births for junctional EB, the incidence is higher than in other countries, possibly reflecting the availability of early molecular genetic diagnostics in severely affected neonates. Dystrophic EB was assessed at 15.58 cases per million live births. The relatively low incidence found for EB simplex, 14.93 per million live births, could be explained by late or missed diagnosis, but also by 33% of cases remaining not otherwise specified. Using log‐linear models, we estimated a prevalence of 54 per million for all EB types, 2.44 for junctional EB, 12.16 for dystrophic EB and 28.44 per million for EB simplex. These figures are comparable to previously reported data from other countries. Conclusions: Altogether, there are at least 2000 patients with EB in the German population. These results should support national policies and pharmaceutical companies in decision‐making, allow more precise planning of drug development and clinical trials, and aid patient advocacy groups in their effort to improve quality of life of people with this orphan disease.